2003
DOI: 10.1038/ncb1063
|View full text |Cite|
|
Sign up to set email alerts
|

Cytochrome c binds to inositol (1,4,5) trisphosphate receptors, amplifying calcium-dependent apoptosis

Abstract: Mitochondrial cytochrome c release and inositol (1,4,5) trisphosphate receptor (InsP(3)R)-mediated calcium release from the endoplasmic reticulum mediate apoptosis in response to specific stimuli. Here we show that cytochrome c binds to the InsP(3)R during apoptosis. Addition of 1 nM cytochrome c blocks calcium-dependent inhibition of InsP(3)R function. Early in apoptosis, cytochrome c translocates to the endoplasmic reticulum where it selectively binds InsP(3)R, resulting in sustained, oscillatory cytosolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
445
4
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 579 publications
(474 citation statements)
references
References 32 publications
23
445
4
2
Order By: Relevance
“…The organelle principally involved in the integration of such stressors, and of proapoptotic and antiapoptotic signals in general, is the mitochondrion, working in close liaison with the endoplasmic reticulum 11,12,39 . Mitochondria are the barometer of the cell, responding to the state of health or disease in all parts of the cell, from the nucleus to the cytoplasm, integrating the disparate stresses to repress or activate the apoptotic pathway.…”
Section: Mitochondrial Rons Influence Cell Deathmentioning
confidence: 99%
“…The organelle principally involved in the integration of such stressors, and of proapoptotic and antiapoptotic signals in general, is the mitochondrion, working in close liaison with the endoplasmic reticulum 11,12,39 . Mitochondria are the barometer of the cell, responding to the state of health or disease in all parts of the cell, from the nucleus to the cytoplasm, integrating the disparate stresses to repress or activate the apoptotic pathway.…”
Section: Mitochondrial Rons Influence Cell Deathmentioning
confidence: 99%
“…For example, mutual interactions between cytochrome c and inositol 1,4,5 triphosphate receptor (InsP 3 R) have been reported that are believed to amplify the apoptotic signals. 20 InsP 3 R is an ER membrane protein responsible for promoting ER Ca 2 þ release into cytosol. It has been proposed that a feed-forward mechanism exists such that early in apoptosis cytochrome c and InsP 3 R interactions promote further releases of Ca 2 þ from the ER into cytosol and subsequent excessive release of cytochrome c from mitochondria, thereby further amplifying the apoptotic effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that a feed-forward mechanism exists such that early in apoptosis cytochrome c and InsP 3 R interactions promote further releases of Ca 2 þ from the ER into cytosol and subsequent excessive release of cytochrome c from mitochondria, thereby further amplifying the apoptotic effects. 20 PUMA is a newer member of the Bcl-2 family and, thus, very little is known about its role in apoptosis that is induced in response to alterations in intracellular Ca 2 þ homeostasis. TG is a sesqueterpene lactone that perturbs calcium (Ca 2 þ ) homeostasis by inhibiting the ER Ca 2 þ ATPases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that these calcium events are coordinated with augmented cytochrome c release. 58 In this scenario, one can suggest that Ca 2 þ released in one cell that has high levels of Bax may serve to send Bax signals to other cells via Ca 2 þ release. Thus, in addition to its intracellular effects, Ca 2 þ would contribute to propagate signals related to perturbations in cytosolic or stored Ca 2 þ levels.…”
Section: Discussionmentioning
confidence: 99%